Robert Kennedy and his times - Schlesinger, Arthur M., Jr. (Arthur Meier), 1917-2007.; Reeves, Richard, 1936- ([New York] : Encyclopedia Americana/CBS News Audio Resource Library, 1978)
Schlesinger discusses Robert Kennedy, American politics in the 1950's and 1960's, and comments on today's American politics and social problems.
Distributed by Grolier Education Corp., New York.
With: Jack Kerouac, king of beat? / Barry Gifford -- Leadership / James M. Burns.
Interviewer, Dick Reeves.
Recorded Sept. 25, 1978, New York.
Preservation master.
Keywords: Kennedy, Robert F., -- 1925-1968.; United States -- Politics and government -- 1945-1989.